Local Wisdom: Pendidikan Kerukunan Umat Beragama Pada Sekolah Dasar di Pulau Doom Kota Sorong - Zulkifli, Zulkifli; Munzir, Munzir; Henraman, Henraman; Imran, Andi; Maima, Thomas (Journal of Islamic Education, 2024)
The purpose of this research is to explore the local wisdom of Satu Tungku Tiga Batu and its integration in religious harmony education. Qualitative research method by describing the real conditions in the implementation of harmony on Doom Island, Sorong City. The results showed that First, the local wisdom of Satu Tungku Tiga Batu encourages and supports dynamic, humanist, and democratic interfaith harmony on Doom Island. Second, the contextualization of religious harmony education in the real life of students can be done by integrating local wisdom values to strengthen the learning materials of elementary school subjects.  The recommendations of this research are as follows: (1) The government should pay more attention to efforts to instill values through education. Government policies in preparing facilities and other needs are sustainable. (2) The value of local wisdom for strengthening elementary school subject learning materials is important for teachers when implementing the Merdeka Curriculum